Development of Automatic System for Apiary - Khrystyuk, Andriy; Kuvshynova, Olena (Моделювання, керування та інформаційні технології, 2019)
The basic stages of development of the remote automatic control system of apiary are given. Stages of development are suggested. Measurement methods are presented and analyzed. The choice of measuring instruments is made.